2017
DOI: 10.1186/s12916-017-0807-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors are major determinants of thrombotic risk in patients with the lupus anticoagulant

Abstract: BackgroundPatients with the lupus anticoagulant (LA) are at an increased risk of thrombotic events, which in turn increase the risk of death. Understanding the determinants of thrombotic risk in patients with LA may pave the way towards targeted thromboprophylaxis. In the Vienna Lupus Anticoagulant and Thrombosis Study (LATS), we systematically evaluate risk factors for thrombotic events in patients with LA.MethodsWe followed 150 patients (mean age: 41.3 years, female gender: n = 122 (81.3%), history of thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…Consistent with this notion, during the observation period of our patients, smoking and diabetes were strong risk factors for developing thrombosis, which therefore represent two potential factors of the aforementioned “second hit phenomenon” [30]. Data from our study do not indicate that TF-bearing EVs contribute to this “second hit.” However, we cannot exclude a role of very low levels of TF-bearing EVs, which cannot be detected with our assay [22].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Consistent with this notion, during the observation period of our patients, smoking and diabetes were strong risk factors for developing thrombosis, which therefore represent two potential factors of the aforementioned “second hit phenomenon” [30]. Data from our study do not indicate that TF-bearing EVs contribute to this “second hit.” However, we cannot exclude a role of very low levels of TF-bearing EVs, which cannot be detected with our assay [22].…”
Section: Discussionsupporting
confidence: 82%
“…Data from experimental studies indicate that a “second prothrombotic hit” might be needed for the development of APS, because in mouse models, elevated antiphospholipid antibodies promoted thrombosis only in presence of vascular damage, endothelial activation, or inflammation [ 28 , 29 ]. Consistent with this notion, during the observation period of our patients, smoking and diabetes were strong risk factors for developing thrombosis, which therefore represent two potential factors of the aforementioned “second hit phenomenon” [ 30 ]. Data from our study do not indicate that TF-bearing EVs contribute to this “second hit.” However, we cannot exclude a role of very low levels of TF-bearing EVs, which cannot be detected with our assay [ 22 ].…”
Section: Discussionsupporting
confidence: 68%
“…Traditional CVD risk factors, including diabetes and smoking, increase the risk of thrombosis in aPL-positive patients (20). Systemic lupus erythematosus itself is an independent risk factor for CVD, which still remains the major cause of mortality in SLE patients (21).…”
Section: Discussionmentioning
confidence: 99%
“…The Vienna Lupus Anticoagulant and Thrombosis Study is an ongoing, prospective, single-center cohort study enrolling adult patients persistently positive for LA (confirmed 12 weeks apart). Details on the study design have been elaborately described before 7,16 . In the current analysis, patients with a history of TE and patients without a history of TE who attended their regular follow-up visits between 2015 and 2017 were asked for new blood samples.…”
Section: Study Populationmentioning
confidence: 99%
“…Nevertheless, not all individuals with LA develop TE 6 . Several other risk factors promoting thrombosis have been identified 7,8 . However, more specific biomarkers are needed to predict and treat individual thrombotic risk.…”
Section: Introductionmentioning
confidence: 99%